Recent Advances on the Multiplex Molecular Detection of Plant Viruses and Viroids - Pallás, Vicente; Sánchez-Navarro, Jesus A.; James, Delano (Frontiers in Microbiology, 2018)
Plant viruses are still one of the main contributors to economic losses in agriculture. It has been estimated that plant viruses can cause as much as 50 billion euros loss worldwide, per year. This situation may be worsened by recent climate change events and the associated changes in disease epidemiology. Reliable and early detection methods are still one of the main and most effective control strategies for plant viral diseases. During the last years considerable progress has been made to develop tools with high specificity and low detection limits for use in the detection of these plant pathogens. Time and cost reductions have been some of the main objectives pursued during the last few years as these increase their feasibility for routine use. Among other strategies these objectives can be achieved by the simultaneous detection and (or) identification of several viruses in a single assay. Nucleic acid-based detection techniques are especially suitable for this purpose. Polyvalent detection has allowed the detection of multiple plant viruses at the genus level. Multiplexing RT-PCR has been optimized for the simultaneous detection of more than ten plant viruses/viroids. In this short review, we provide an update on the progress made during the last decade on techniques such as multiplex polymerase chain reaction (PCR), polyvalent PCR, nonisotopic molecular hybridization techniques, real-time PCR, and array technologies to allow simultaneous detection of multiple plant viruses. Also, the potential and benefits of the powerful new technique of deep sequencing/next-generation sequencing are described.